(3cjajI EYOGO GdHMhK GdLGeYjI aj GdYdhe GdGbJUGOjIs - (3aGQS(B, (3aVjds ((3GdLRGFQ(B:s (3OGQ CLjGd GdQbej (B,s, 2023)
(3jaUd gPG GdcJGH aj eLedg WQb hcjajI GYOGO GdHMhK GdLGeYjI ef JbQjQ JQHUGJ, ePcQGJ eGSJQ, CWQhMGJ GdOcJhQGg, ebGdGJ YdejI, eWHhYGJ HjOGZhLjI heOGNdGJ YdejI hPdc ef NdGd YTQI eMGhQ hgj cGdJGdj(B: (3GdeQMdI GdJegjOjI dYedjI EYOGO GdHMK GdLGeYj, CfhGY GdHMhK GdLGeYjI, GNJjGQ hVHW ehVhY GdHMK, CgejI NWI GdHMK hechfGJgG, GdeUGOQ hGdeQGLY hcjajI GdGSJaGOI efgG, COhGJ LeY GdeYdheGJ GdChdjI, GdGbJHGS hGdJgejT, TQhW cJGHI GdHMK hCSdhH GdcJGHI GdYdejI, GdTcd GdfgGFj ddHMhK GdLGeYjI, ELQGAGJ hMjKjGJ Jbhje GdHMhK GdLGeYjIs
(3HHdjhZQGajG(B:(3U U(B.439-444s
Keywords: (3GdHMhK GdYdejIs; (3efgLjIs